43.5k views
3 votes
Using substitution or elimination 3y=-1/2x+2. y=-x+9

User Deepak Jha
by
4.8k points

1 Answer

5 votes

Answer:

(x, y) = (10, - 1)

Explanation:

given the 2 equations

3y = -
(1)/(2) x + 2 → (1)

y = - x + 9 → (2)

substitute y = - x + 9 into (1)

3(- x + 9) = -
(1)/(2) x + 2

- 3x + 27 = -
(1)/(2) x + 2

add
(1)/(2) x to both sides

-
(5)/(2) x + 27 = 2 ( subtract 27 from both sides )

-
(5)/(2) x = - 25

multiply both sides by 2 and divide by - 5

x = 10

solution (10, - 1)


User Ellitt
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.